Upaya Meningkatkan Kemampuan Motorik Halus Melalui Kegiatan Mewarnai di Kelompok B1 TK Berkah Kota Jambi Tahun 2016/2017 - Warnida Warnida (Universitas Batanghari Jambi, 2019)
This study aims to improve fine motor skills through coloring activities in group B1 TK Blessings of Jambi City. Fine motor skills are very important to support further education. This research is classroom action research conducted in 2 cycles. The subjects of this study were 16 children of B1 TK Berkah Kota Jambi group with objects of fine motor skills. Data collection techniques used are observation and documentation. Data analysis using descriptive qualitative and quantitative. Observation results of fine motor skills before the average action percentage of 64.58% with BSH criteria, experienced an increase of 3.65% in the first cycle was in the criteria of BSH, in the second cycle there was an increase of 11.72% to BSB. Based on these data it can be concluded that the fine motoric abilities of children have increased and achieved success indicators of more than 75% with Very Good Developing criteria. The success is inseparable from the learning steps, namely: (1) One class is divided into 3 groups consisting of 4-5 children (2) Each group gets 4-5 kinds of dyes that have been placed in the container (3) The teacher provides examples of coloring activities what will be done (4) Delivering the agreed-upon rules during the coloring activity and (5) Colored images tailored to the ongoing theme in the TK